2006
DOI: 10.1021/jp056697y
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the Neurotransmitter, Neuropeptide Y, with Phospholipid Membranes:  Film Balance and Fluorescence Microscopy Studies

Abstract: The association of neuropeptide Y (NPY) with air/water interfaces and with phospholipid monolayers on water subphases and on physiological buffer has been investigated. Surface pressure (π) vs. molecular area (A) relations of the peptide at water surfaces depend on the concentration of the spreading solutions. Independent of that concentration, they show a transition from a low-density state to a high-density state at π ∼ 12 mN/m. Similar features are observed in the NPY adsorption to preformed monolayers (Δπ(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
32
0
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 43 publications
(73 reference statements)
4
32
0
4
Order By: Relevance
“…As reported in the literature, the lipid dye Rh-DHPE (l exc = 561 nm) is largely excluded from ordered phases in mono-and bilayer membranes (e.g., liquid condensed phases [15,17] ). In Figure 2 B, Rh-DHPE is preferentially incorporated into the polymer-enriched phase (compare with Figure 2 A) which indicates a less-ordered phase state, whereas the black patches in Figure 2 A,B consist of a moreordered DPPC-enriched phase.…”
mentioning
confidence: 61%
“…As reported in the literature, the lipid dye Rh-DHPE (l exc = 561 nm) is largely excluded from ordered phases in mono-and bilayer membranes (e.g., liquid condensed phases [15,17] ). In Figure 2 B, Rh-DHPE is preferentially incorporated into the polymer-enriched phase (compare with Figure 2 A) which indicates a less-ordered phase state, whereas the black patches in Figure 2 A,B consist of a moreordered DPPC-enriched phase.…”
mentioning
confidence: 61%
“…1 The surface thermodynamics of NPY shows that the peptide interacts strongly with lipid monolayers and suggested that this interaction is similar with zwitterionic and with anionic lipids. 4 As we look into the molecular details with IRRAS, however, it becomes clear in this work that the peptide interacts substantially stronger with DMPS − than with DPPC. Among other implications, this may provide for a mechanism which facilitates receptor binding once the transmitter encounters the receptor in the trajectory of its 2D random walk along the membrane surface.…”
Section: Discussionmentioning
confidence: 82%
“…Among other implications, this may provide for a mechanism which facilitates receptor binding once the transmitter encounters the receptor in the trajectory of its 2D random walk along the membrane surface. 4 The IRRAS results presented here help to characterize the underlying interactions in molecular detail and to provide more definite answers regarding the association of the peptide with the biomimetic model surfaces.…”
Section: Discussionmentioning
confidence: 89%
“…Surface pressure-area isotherms of the monolayers were obtained using a thermostated Langmuir film balance of home made design (Dyck and Lösche, 2006) at a subphase temperature of 20 • C. The studies of the mesoscopic morphology of the monolayer were performed with a Zeiss Axiotech Vario epifluorescence microscope (dye NBD C 12 -HPC, Molecular Probes, Leiden, The Netherlands), associated with the film balance (Krüger et al, 1999) The dissolved DPPC and the DPPC/DPPS mixtures were spread on the subphase and the solvent was allowed to evaporate for at least 10 min. The monolayers were compressed typically at a barrier speed that corresponded to approximately 2 Å 2 /(molecule min) and the surface pressure was monitored continuously.…”
Section: Isotherms and Fluorescence Microscopymentioning
confidence: 99%